A reoccupation of an empty place – nation in early 20th century Polish National-Democratic discourse and political modernity - Marzec, Wiktor (Hybris, 2014)
This article examines a diachronic change in political thought of Polish National Democracy between its emergence as a coherent political movement and the final crystallization of its political program after the 1905 Revolution. It scrutinizes it as a [failed] answer for the political modernity, seen as a condition of groundlessness of the social and a radical contingency of the political. I argue that such a comprehension can shed light on reasons for deep alternations in the structure of national-democratic thought. From progressive social radicalism, through politically envisioned nation-building, they turned into exclusionary and xenophobic nationalism. The change was ushered by the urgent need for a foundation for political thinking, ultimate envisioning of the society as a closed, positively defined entity and reinventing the teleological horizon. A reoccupation of the place of legitimacy of the social order by a biologically conceptualized nation followed. This reoccupation of the old structure of thought, imprinting itself on the new ideas facing contingency, prevented an adequate confrontation with political modernity and lead national democracy to an authoritarian turn, simultaneously „closing” the concept of the nation in Polish political thinking for years.